Critical Notice: Why Killing Is Not Always Worse—and Is Sometimes Better—Than Letting Die - Kuhse, Helga (1998)
The philosophical debate over the moral difference between killing and letting die has obvious relevance for the contemporary public debate over voluntary euthanasia. Winston Nesbitt claims to have shown that killing someone is, other things being equal, always worse than allowing someone to die. But this conclusion is illegitimate. While Nesbitt is correct when he suggests that killing is sometimes worse than letting die, this is not always the case. In this article, I argue that there are occasions when it is better to kill than to let die.